2016
DOI: 10.1016/j.cmpb.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for the automated segmentation and volume quantification of cardiac fats on computed tomography

Abstract: The deposits of fat on the surroundings of the heart are correlated to several health risk factors such as atherosclerosis, carotid stiffness, coronary artery calcification, atrial fibrillation and many others. These deposits vary unrelated to obesity, which reinforces its direct segmentation for further quantification. However, manual segmentation of these fats has not been widely deployed in clinical practice due to the required human workload and consequential high cost of physicians and technicians. In thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 49 publications
0
90
0
2
Order By: Relevance
“…In this work, we used the cardiac CT dataset from [22]. To properly evaluate the cardiac fat of the CT scans, all of the raw images in this dataset were transferred to (-200, -30) the HU range to keep the cardiac fat more obvious.…”
Section: A Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we used the cardiac CT dataset from [22]. To properly evaluate the cardiac fat of the CT scans, all of the raw images in this dataset were transferred to (-200, -30) the HU range to keep the cardiac fat more obvious.…”
Section: A Data Descriptionmentioning
confidence: 99%
“…Rodrigues et al investigated the feature extraction method comprising of classification and registration algorithms for automatic segmentation and quantification of epicardial fat. This method can obtain an ideal performance in the Dice similarity index [22], where the procedures are some what complicated. For the results of cross-validation on another patient, it can be observed that the epicardial fat is oversegmented on the cardiac CT image, which affects the effectiveness of segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…In this subsection, a practical experiment using computed tomography (CT) images is performed. In a previous work [19], we proposed a method that automatically segments two types of cardiac fats: epicardial and mediastinal.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…The goal is to find an optimal or an appropriate near optimal transformation of one image causing it to resemble the whole or part of the other [1]. In regards to pattern recognition, the goal is to align landmarks between two images [17] or to use similarity measures to find the most suitable position of a template [18, 19]. 3D reconstruction and geometry estimation can also involve the use of search for specific areas and patterns [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…TAATotal abdominal fat attenuation: mean attenuation value within the abdominal fat, in HU (ND).TAA_HUFat(thoracic)− 190 to − 30 HUEpicardial fat area: fat located between the heart and the pericardium, in mm 2 [94–100]. Random forest [101, 102], geodesic active contours [103], fuzzy C-means [104], other [105]EFAEpicardial fat attenuation: mean attenuation value within the epicardial fat, in HU [106]EFA_HU…”
Section: Introductionmentioning
confidence: 99%